(Physico chemical constants of some Indonesian essential oils and their GLC Finger Prints on OV Silicone 101 as Liquid Phase) - Nurlydia, Dede; Dharma, Gasik; Moestafa, Achmad (Balai Besar Industri Agro, 1993)
Essential oils are volatile derived from plants, therefore Glc method of analysis is most recommended.Each oil have differentcomponents and quantitatively can be used as a standard if the same procedure is followed.In case from the different sample different